Moral leadership for a divided age: fourteen people who dared to change our world - Gushee, David P. (Brazos Press, a division of Baker Publishing Group, 2018)
"Examines the lives of great leaders of recent centuries to offer models of moral leadership, helping readers discover lessons for their own lives and times"--